THE EFFECTIVENESS OF ONLINE BRAINWRITING AND BRAINSTORMING TECHNIQUES IN TEACHING WRITING TO STUDENTS WITH DIFFERENT LEARNING STRATEGIES - Hermasari, Devi; Mujiyanto, Yan (English Education Journal, 2015)
This current study tried to examine online brainwriting compared to brainstorming as prewriting strategies in improving the writing skills of students with high and low frequency of LLS. 2 x 2 factorial design of experimental research was carried out to collect the data from 60 college students majoring in Dance Education. Two experimental groups, A and B, were given two different treatments: online brainwriting and brainstorming. SILL by Oxford (1990) was used to determine whether the students have high or low frequency of LLS.The ANOVA test showed Ï=0.000 for both online brainwriting and brainstorming which prove effectiveness of both techniques. It is also found that online brainwriting is proven to be significant for both high and low frequency of LLS students with Ï=0.000. Brainstorming, on the other side, is only significant for high frequency of LLS students with Ï=0.000, yet is proven insignificant for low frequency of LLS students with Ï=0.039.Â  However, the results showed there was no interaction between the use of prewriting strategies and the frequency of LLS which was proven by the Ï=0.529. Future researchers might consider having a mixed method of study in comparing those two strategies to get more precise results.